BUDGET ACCOUNTING REFORMS IN UZBEKISTAN AND THEIR SIGNIFICANCE - Yakubov Valijon Ganiyevich (Modern American Journals, 2025)
The article examines the reforms being carried out in the field of budget accounting in Uzbekistan and their significance. In the course of the study, we will discuss how the budget accounting system is being modernized to make it more convenient, understandable, and effective. This will help bring it into line with international standards, including International Accounting Standards (IAS) for the public sector. We will also consider how budget expenditure accounting, control, and analysis are carried out. We will analyze how reforms contribute to increasing economic efficiency, making the system more transparent, combating corruption, and developing international cooperation. During the discussion, we will consider the prospects for the development of the budget accounting system in Uzbekistan. In particular, we will talk about the application of artificial intelligence and big data analysis, as well as the introduction of innovative approaches such as "civil budget."
Keywords: Budget accounting, financial reforms, Uzbekistan's economy, budget expenditures, accounting system, public funds, transparency, efficiency.